Increasing consumer surplus through a novel product testing mechanism - Ulrike Vollstaedt; Patrick Imcke; Franziska Brendel; Christiane Ehses-Friedrich (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
Our study proposes a novel mechanism to reduce information asymmetry about product quality between buyers and sellers. Product testing organizations like Consumer Reports (US) and Stiftung Warentest (Germany) seek to reduce this asymmetry by providing credible information. However, limited capacity leads to testing of only a select number of product models, often bestsellers, which can yield suboptimal information. After outlining our mechanism, we develop a game to derive testable predictions. We show theoretically that a unique Nash equilibrium exists in which our mechanism yields optimal information, equivalent to a world of complete information, while selecting bestsellers does not. Subsequently, we confirm experimentally that our mechanism increases consumer surplus. – – In dieser Studie schlagen wir einen neuartigen Mechanismus zur Verringerung der Informationsasymmetrie bezüglich der Produktqualität zwischen Käufern und Verkäufern vor. Produkttestorganisationen wie Consumer Reports (USA) und Stiftung Warentest (Deutschland) versuchen, diese Asymmetrie durch die Bereitstellung glaubwürdiger Informationen zu verringern. Begrenzte Kapazitäten führen jedoch dazu, dass nur eine ausgewählte Anzahl von Produktmodellen, oft Bestseller, getestet werden, was zu suboptimalen Informationen führen kann. Nachdem wir unseren Mechanismus skizzieren, entwickeln wir ein Spiel um überprüfbare Vorhersagen herzuleiten. Wir zeigen theoretisch, dass es ein eindeutiges Nash-Gleichgewicht gibt, in dem unser Mechanismus optimale Informationen bereitstellt, was einer Welt vollständiger Informationen entspricht, während die Auswahl von Bestsellern dies nicht tut. Anschließend bestätigen wir experimentell, dass unser Mechanismus die Konsumentenrente erhöht.
Keywords: C72; C91; D82; L15; 330; Consumer surplus; information asymmetry; product quality; product test; information disclosure; mechanism design; experiment